A novel metamaterial with tension-torsion coupling effect. (5th June 2019) - Zheng, Bin-Bin; Zhong, Rong-Chang; Chen, Xuan; Fu, Ming-Hui; Hu, Ling-Ling
Abstract: A novel 3D metamaterial with tension-torsion coupling effect is designed through connecting neighbor chiral honeycomb layers by inclined rods. Both numerical simulation and experiment analysis show the tension-torsion coupling effect of the metamaterial is much better compared to other metamaterials we can find in literatures. With the increase of cells number, the tension-torsion coupling effect of this metamaterial at the strain of 1% increases firstly, reaching the perk value of 11.36°, then decreases slowly, and it remains an appreciable value of 4.44° even when the cells number is 25 × 25 × 25. Analysis shows that size effect in the thickness direction can be neglected when the layers number is more than 5. The stress and deformation of struts within the metamaterial are investigated. For the inclined rods and the square loops, their main deformation is the axial deformation while the main deformation of ligaments is out-of-plane bending deformation. According to the deformation law of inclined rods, it can be concluded that when the compression strain increases, the inclined rods lying in the layer's center enter the instability state first and then instability zone expands outwards, resulting in instability state of the metamaterial. Graphical abstract: Unlabelled Image Highlights: A novel 3D metamaterial with outstanding tension-torsion coupling effect is designed and fabricated. The torsion angle of metamaterial can maintain an appreciable value even when cells number is large. The deformation modes and deformation mechanisms of the metamaterial are investigated. The design concept provides a framework to develop tension-torsion coupling metamaterials.